Blood Pressure Phenotype Variations at Different Gestational Stages and Associated Pregnancy Risks - Zuo, Lushu; Fang, Yiwen; Li, Linjie; Duan, Hongli; Wen, Jiying; Yang, Qing; Han, Cha; Lv, Lijuan; Zhou, Xin (American journal of hypertension, 2025)
Hypertensive disorders of pregnancy (HDP) significantly increase the risk of adverse pregnancy outcomes (APOs). Blood pressure (BP) phenotypes, including masked hypertension (MH), white-coat hypertension (WCH), sustained hypertension (SH), and normotension, are identified through office BP (OBP) and ambulatory BP (ABP) monitoring. The proportion of BP phenotypes at different gestational age and their associations with APOs are not well understood. This retrospective study included 967 women at high risk or diagnosed with HDP who underwent OBP and ABP measurement at different gestational stages [0-19+6 (n = 150), 20+0-29+6 (n = 221), 30+0-32+6 (n = 135), 33+0-35+6 (n = 185), and ≥36+0 gestational weeks (GW) (n = 276)]. Women with ABP monitored at 20+0-29+6 GW had the lowest BP levels corresponding to the highest prevalence of NT. Compared to OBP, hypertension determined by ABP demonstrated stronger and more consistent associations with APOs, defined as a composite of maternal (e.g., severe preeclampsia, preterm birth) and fetal (pregnancy loss and SGA infants) outcomes. SH was consistently associated with the highest risk for APOs, with risk decreasing as gestation advanced after 20+0 GW. MH was significantly associated with APOs, particularly between 30+0 and 32+6 GW. WCH had no association with fetal outcomes at any gestational stage. The associations between BP phenotypes and APOs differ across gestational stages. SH detected earlier in pregnancy carries the highest risks, while WCH is generally benign for fetal outcomes. These findings highlight the critical role of ABP monitoring in BP phenotyping and underscore the need for gestational-stage-specific diagnostic thresholds to enable tailored interventions and optimize APOs.